Un umbone di scudo da parata in bronzo dorato da Nocera Umbra: nuove considerazioni su un manufatto venuto da lontano (Gilgameš, 2016)
How many artifacts do we prefer to forget because of the many questions which arise in relation to production, dating and origin? This study aims to draw attention on the shield boss in gilded bronze found in the Tomb 1 of the Nocera Umbra’s necropolis. This burial is one of the most rich of the early medieval cemetery. It enumerates among the funeral goods a shield boss which is characterized by a central frieze with battle scenes realized with an openwork decoration. To date similar shield bosses have not been yet discovered neither in Italy nor outside. So despite its uniqueness in the archaeology field and in the art historical one, it has been forgotten for many years. The impossibility to compare the Nocera Umbra’s shield boss with similar ones does not allow to add it accurately within time-space coordinates.A significant help comes only from an iconographic and stylistic research. The shield boss may be connected indeed to the artistic production of the Late Antiquity period and of the Early Byzantine one only comparing it with artifacts belonging to other categories as well as silver plates, buckles. The depth study of this object emphasizes therefore the complexity of rebuilding the circumstances and the productive context of valuable artifacts if we limit ourselves to just one field of study. A multidisciplinary approach which makes dialoguing archaeology and art history becomes more and more significant in the construction of the Late Antique and the Early Byzantine world.